Level of Basic Soccer Skills Among 14-Year-Old Players at SSB PS Unimuda Sorong - Jimmy Aronggear; Waskito Aji Suryo Putro; Saiful Anwar; Harmaman Harmaman; Leo Pratama (Jurnal Porkes, 2026)
Background. Basic technical skills form the foundation of soccer and determine a player’s performance quality, particularly during the developmental years (ages 13–17). Uneven mastery of these techniques among young players is a persistent challenge in youth academy training and necessitates measurable, objective evaluation. Objective. This study aims to analyze the level of basic soccer technical skills among 14-year-old players at SSB PS Unimuda Sorong based on five main components: passing, dribbling, heading, ball control, and shooting. The central research question is: “What is the level of basic technical skills among 14-year-old soccer players at SSB PS Unimuda Sorong across five technical components?”  Methods. A quantitative descriptive survey design was employed. The sample comprised 35 players selected via total sampling. Data were collected through standardized tests and measurements, then analyzed using descriptive statistics (frequency, percentage, mean, and standard deviation) to categorize players’ skill levels into good, average, or poor categories based on established norms. Results. Overall, 51.4% of players were categorized as “good” and 41.8% as “average.” Shooting was the strongest skill (57.1% good; M = 8.46, SD = 1.12), while heading was the weakest (2.9% good; M = 3.34, SD = 0.87), with all 35 players falling in the average category for ball control (M = 15.20, SD = 2.43). Conclusion. Basic technical skills among 14-year-old players at SSB PS Unimuda Sorong are at a sufficiently good but unevenly distributed level. Heading and ball control require the most targeted intervention. Coaches are recommended to integrate specific heading drills and multi-contact ball control exercises into the weekly training program. Future research should adopt experimental designs to examine the effects of structured interventions on identified technical weaknesses.